Sud de Chantal Akerman ou une histoire de territoire et de terre : le Sud comme espace de mémoire - Marie Liénard (Anglophonia, 2006)
The article examines Chantal Akerman's work Sud (South) filmed in 1999. The Belgian filmmaker had always been fascinated by the Southern part of the United States. Her film retraces her journey through time and space, and explores what she calls her "obsession" with History and memory. "Sud," she writes, "takes up the questions and the quest for meaning beyond the nonsense of barbarism and death." The film focuses on the lynching of James Byrd in Jasper, Texas, which is used as the departure point of the search for her own history of suffering and mourning. The paper analyses how Akerman’s Sud transforms the American place into a space of memory by inscribing it into a European history beyond the myth created by the Southern imagination.